“Ritme Zaman Kini: Kajian Musik Modern sebagai Medium Ideologi dan Gaya Hidup” - Adha, Yasril (Institut Seni Indonesia Padangpanjang, 2025)
Modern music functions not only as a form of artistic expression but also as an ideological medium and a marker of lifestyle in contemporary society. This article explores how modern music—including genres such as pop, rock, hip hop, and EDM—has evolved into a social communication tool that reflects values, identities, and aspirations of today’s urban generation. Using a qualitative approach and literature review, the study examines the relationship between music, media, and popular culture, and how the music industry fosters communities, social resistance, and identity construction. The research also highlights the role of digital media and algorithms in transforming patterns of music production and consumption, resulting in music that is simultaneously personalized and commodified. Modern music has become more than entertainment; it is an ideological arena where meanings are negotiated between producers, consumers, and cultural institutions. The study reveals that the rhythms and lyrics of modern music often carry messages of freedom, social critique, alternative spirituality, and even consumerism. By analyzing modern music as a cultural discourse, this article uncovers its potential as a medium for shaping social consciousness and as a continuously evolving form of global lifestyle.